Bioprocess optimization for cell mass production and functional characterisation of: Lactobacillus plantarum - Othman, N.; Chan, Stephanie; Malek, R.; Ramli, S.; Ismail, N.; Sarmidi, M.; Aziz, R.; El Enshasy, H. (2012)
Probiotic bacteria are beneficial microbes which help to encourage the development of mammalian immunity system and also enhance gastrointestinal and bowel system in stomach. The study was conducted to design and establish industrial platform for high cell density cultivation as the demand of the probiotic cells. The optimized medium that supports high cell biomass was used to study the growth kinetics of Lactobacillus plantarumin in the shake flask. This medium had the following composition (g L-1): glucose, 30; meat extract, 4; yeast extract, 7; sodium acetate, 5; K2HPO4, 2; (NH4)2SO4, 2; MgSO4.7H2O, 0.2; MnSO4.4H2O 0.05. Furthermore, the optimized medium was used for batch cultivation in semi industrial scale 16-L stirred tank bioreactor under controlled and uncontrolled pH conditions. Cultivation of L. plantarum in the shake flask yielded cell mass of about 3.46 g L-1 concomitant high lactic acid of 12.7 gL-1. In bioreactor cultures, the maximum cell mass of 4.49 g L-1 was obtained when cultivation was conducted under controlled pH compared to only 2.34 g L-1 in uncontrolled pH culture. Data showed that the specific growth rate of this strain increased from only 0.37 h-1 in shake flask culture up to 0.6369 h-1 when cells cultivated in bioreactor under controlled pH condition. The funtional characteristics such as the effect of gastric juice, pH and bile salts of the produced cells were also evaluated. L. plantarum showed moderate tolerance to SGJ with cell viabilty of 31.28%, 37.56%, 42.86% and 54.33% at pH 1, 2, 3 and 4, respectively. This strain showed high tolerance to bile salt concentration range from 0.5% up to 3%. However when cells incubated at solution of bile salt concentration of 4%, cell viability was reduced by about 50%. Moreover, this probiotic bacteria is susceptibility to antibiotics such as streptomycin, tetracycline, erythromycin, and rifampicin. Therefore they will not create any potential to transmit antibiotic resistance genes to other bacteria in gastrointestinal tract especially to the pathogenic microorganisms. Based on these data we can conclude that the strain produced in this study could have many potential application as probiotic and as starter culture in nutraceuticals, food and feed industries.